Kesenian Senjang Dan Rejung Sebagai Bagian Dari Tradisi Masyarakat Uluan Musi - Yadri Irwansyah, Sarkowi, Haikal Saputra, Yoga Alvin Almada (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2025)
This research is an article about the revitalization of senjang and rejung arts as part of the traditions of the uluan Musi community. Senjang and rejung themselves are types of spoken literary arts that developed in the people of South Sumatra, especially the Uluan Musi area. The efforts to answer the problems and analysis in this paper were carried out using qualitative methods through processes and procedures starting from collecting data through interviews, observation, documentation, then carrying out data analysis, and checking the validity of the data. From this research, the author discovered the fact that the arts of senjang and rejung are starting to be abandoned by their supporting communities and are threatened with extinction, because the Uluan Musi community is more interested in using modern music in various activities. The steps for revitalizing the arts include local content learning from primary to secondary school levels, carrying out various events and artistic activities that include the arts of sejang and rejung.